Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1371/journal.ppat.1004888
|View full text |Cite
|
Sign up to set email alerts
|

Admixture in Humans of Two Divergent Plasmodium knowlesi Populations Associated with Different Macaque Host Species

Abstract: Human malaria parasite species were originally acquired from other primate hosts and subsequently became endemic, then spread throughout large parts of the world. A major zoonosis is now occurring with Plasmodium knowlesi from macaques in Southeast Asia, with a recent acceleration in numbers of reported cases particularly in Malaysia. To investigate the parasite population genetics, we developed sensitive and species-specific microsatellite genotyping protocols and applied these to analysis of samples from 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
104
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(117 citation statements)
references
References 48 publications
(57 reference statements)
12
104
0
Order By: Relevance
“…Generally, there are low levels of complexity per infection in clinical P. knowlesi isolates, most containing one predominant haploid genotype each (Table S3). The estimates of within-infection genomic complexity (1 − F WS ) were similar for cluster 1 and cluster 2 isolates [mean within-infection fixation index (F WS ) values of 0.94 and 0.95 respectively; MannWhitney test; P = 0.40] and correlated highly with indices independently derived by counting the number of distinct alleles in a previously performed 10-locus microsatellite genotypic analysis (Pearson's r 2 = 0.76, P = 6.4 × 10 −10 ) (Table S3) (18). Despite the differences in overall nucleotide diversity in the different clusters, the relative proportions of synonymous, nonsynonymous, intronic, and intergenic SNPs observed were similar in each (respectively 14%, 16%, 13%, and 57% for cluster 1; 14%, 17%, 13%, and 56% for cluster 2; and 13%, 18%, 14%, and 55% for cluster 3).…”
Section: Resultsmentioning
confidence: 67%
See 2 more Smart Citations
“…Generally, there are low levels of complexity per infection in clinical P. knowlesi isolates, most containing one predominant haploid genotype each (Table S3). The estimates of within-infection genomic complexity (1 − F WS ) were similar for cluster 1 and cluster 2 isolates [mean within-infection fixation index (F WS ) values of 0.94 and 0.95 respectively; MannWhitney test; P = 0.40] and correlated highly with indices independently derived by counting the number of distinct alleles in a previously performed 10-locus microsatellite genotypic analysis (Pearson's r 2 = 0.76, P = 6.4 × 10 −10 ) (Table S3) (18). Despite the differences in overall nucleotide diversity in the different clusters, the relative proportions of synonymous, nonsynonymous, intronic, and intergenic SNPs observed were similar in each (respectively 14%, 16%, 13%, and 57% for cluster 1; 14%, 17%, 13%, and 56% for cluster 2; and 13%, 18%, 14%, and 55% for cluster 3).…”
Section: Resultsmentioning
confidence: 67%
“…S2). The assignment of the clinical isolates into two distinct clusters shown here also was compared with an independent assignment recently performed using a STRUCTURE analysis of 10-locus microsatellite genotype data for 40 of the 48 isolates (18). All isolates had the same cluster assignment by both methods, except for one cluster 1 isolate, which had an intermediate cluster assignment in the microsatellite analysis (Fig.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…A recent study by Divis et al (2015), high genetic differences were observed among P. knowlesi isolated from macaque in Borneo and Peninsular Malaysia. In a study by Muehlenbein et al (2015), Plasmodium parasites isolated from M. fascicularis and M. nemestrina in Sabah showed significant difference suggesting genetic specificity to different host species.…”
Section: Prevalence Of Plasmodium Knowlesi Among Macaques In Malaysiamentioning
confidence: 93%
“…P. knowlesi can be fatal in case of severe clinical malaria (Cox-Sing et al, 2008). The increase in number of identified cases is due to the availability of better diagnostic tools and the increase in transmission of P. knowlesi from macaques host to humans via mosquitoes (Divis et al, 2015). Its symptoms among humans may be found similar to other malaria parasites (Moyes et al, 2014).…”
mentioning
confidence: 99%